Capitonnage Versus Non‐Capitonnage in Pediatric Pulmonary Hydatid Disease: A Systematic Review and Meta‐Analysis - Mohammad Javad Boozhmehrani; Seyed Sobhan Bahreiny; Mohammad Navid Bastani; Mahdi Amraei; Zahra Mansouri; Razieh Kazemzadeh; Majid Farhadi; Akbar Hoseinnejad; Ali Pirsadeghi; Zahra Asadi; Afshin Bighamian; Gilda Eslami (Health Science Reports)
ABSTRACT Background and Aim Pulmonary hydatid disease, caused by Echinococcus granulosus, presents significant clinical challenges, particularly in pediatric populations. Surgical intervention remains the gold standard for treatment, with various techniques employed, including capitonnage and non‐capitonnage methods. This systematic review and meta‐analysis evaluates the efficacy and safety of capitonnage compared to non‐capitonnage techniques in children. Methods This systematic review and meta‐analysis followed the PRISMA guidelines to ensure methodological rigor. A comprehensive literature search was conducted across PubMed, Web of Science, and Scopus databases to identify relevant studies. To assess pooled event rates and corresponding 95% confidence intervals for both complications and cure rates, we employed a random‐effects model, allowing for variability among study populations. All statistical analyses were conducted using Comprehensive Meta‐Analysis software (version 3.7). Results Thirteen studies met the established inclusion criteria for analysis. The overall complication rate was 46%, with significantly lower rates in the capitonnage group (24%) compared to the non‐capitonnage group (58%). The cure rate was higher in the capitonnage group (83.5%) than in the non‐capitonnage group (65.2%). Meta‐regression analysis indicated that complication rates were influenced by cyst diameter, study publication date, mean age, and type of surgery. Conclusion The findings suggest that capitonnage is associated with better outcomes in terms of lower complication rates and higher cure rates. This evidence supports the use of capitonnage as a preferred surgical technique for managing pulmonary hydatid disease in children. Further research is recommended to explore the long‐term outcomes and potential benefits of combining surgical and pharmacological treatments.